Prevalence of subclinical mastitis and its association with bacteria and risk factors in lactating cows of Barisal district in Bangladesh - Kayesh, Mohammad; Talukder, Milton; Anower, AKM (International Journal of Biological Research, 2014)
The subclinical mastitis is more serious and is responsible for much greater loss to the dairy industry in Bangladesh. This study was per-formed to determine the prevalence of bovine subclinical mastitis and to isolate and identify the bacterial agents and risk factors associated with subclinical mastitis in randomly selected 200 lactating cows (147 local zebu and 53 crossbreds) of Barisal district in Bangladesh. California Mastitis Test (CMT) was performed on each quarter sample of lactating cows at field condition for determination of subclinical mastitis. Out of 200 lactating cows, 57 were found to be positive for subclinical mastitis by CMT. Out of 57 CMT positive cows, only 15 cows showed strong positive reactions and these samples were used for bacteriological culture to isolate and identify bacterial agents. The overall prevalence of subclinical mastitis was 28.50%. The prevalence of subclinical mastitis was significantly high in crossbreds (45.28%) compared to local zebu (22.45%) (p < 0.05). Based on CMT results of quarters, prevalence of subclinical mastitis was 40.57% (n=212) in crossbreds and 20.92% (n=588) in local zebu cows. The prevalence was significantly (p < 0.05) higher in cows with a daily milk yield of 3-5L and 5-7L. The highest prevalence found in mid lactation was 32.50% and the highest prevalence in the age group of 7 to 9 years was 37.50%. The prevalence of subclinical mastitis was comparatively higher (32.69%) in lactating cows where housed with earthen floor compared to concrete floor (23.17%). Among the pathogens isolated from the strongly positive subclinical mastitis samples, the most frequent bacteria were Staphylococcus spp. (73.33%). For early detection of subclinical mastitis, CMT can be performed regularly as a control measure and emphasis should be given on farm management practices, particularly on milking procedure and udder sanitation. Keywords: Bacteria, CMT, Prevalence, Risk factors, Subclinical mastitis.